AVERAGE LIFETIME AND AGE SPECTRA OF DETRITAL GRAINS: TOWARD A UNIFYING THEORY OF SEDIMENTARY PARTICLES - Kowalewski M.; Rimstidt J.D. (My University, 2003)
The observed average lifetime of minerals, as estimated by the average survival time of dated detrital grains, correlates linearly with D sub C estimated from dissolution rates of minerals but does not correlate with D sub H estimated by mineral hardness. The best predictor of the observed average lifetime is the total durability, an estimator that combines D sub C and D sub H indices. The age spectra of grains (i.e., age frequency distributions of radiometrically dated detrital minerals) tend to be right skewed, as predicted by the exponential model used to describe the lifetime of mechanical parts (Weibull function) or the radioactive decay of atoms. Consistent with the model, the less durable grains produce age spectra that are more right skewed and leptokurtic and may yield more accurate estimates of depositional age, whereas the more durable grains often depart from the exponential model, and their age spectra primarily reflect long-term geological changes in the rate of grain production. The integration of geochronological dates and laboratory mineralogical data indicates that the basic statistical parameters of age spectra of dated grains can be estimated and modeled in a quantitative way. The average lifetimes of detrital grains can be quantified from intrinsic properties of minerals, and these quantitative estimates agree well with the qualitative predictions of the classic weathering sequence of Goldich. [PUBLICATION ABSTRACT]
Keywords: SEDIMENTS; MINERALS; STONE; GEOLOGICAL TIME